(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2025)
A wideband double-sided printed dipole antenna is presented. The antenna is a printed dipole fed by a Microstrip tapered balun. The antenna consists of a tapered balun and a dipole with its arms being printed on opposite sides of the dielectric substrate. The total length of the dipole is 48mm, which is approximately half the guided wavelength at 2.4GHz. A two-element array is also presented by combining two dipoles with a Wilkinson power divider. The achievable –10 dB bandwidth is approximately 21% and 20% for the dipole and array antennas, respectively. The realized gains are 2.5 dB and 3.5 dB, respectively.